Pendekatan Pembelajaran Realistic Mathematics Education (RME) dan Kemampuan Komunikasi Matematis - Utami, Nita Putri; Aulia, Silmi; Yulia, Yulia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Realistic Mathematics Education (RME) learning approach is widely used to improve various abilities in the learning process. One of them is mathematical communication skills. The purpose of this study was to determine the contribution of the Realistic Mathematics Education (RME) learning approach in improving mathematical communication skills. This type of research is library research. There are 32 sources in the form of books, journals and proceedings which are edited, organized and research findings. The results obtained are that in the first step, RME understands contextual problems and is able to hone indicators of mathematical communication skills, namely expressing mathematical ideas through oral and written. In the second step, solving contextual problems is able to hone the second indicator of communication skills, namely the ability to understand, interpret, and evaluate mathematical ideas. In the third step, comparing and discussing answers is able to hone the third indicator of mathematical communication skills, namely the ability to use terms, mathematical notation and structures to present ideas, describe relationships and model situations. In the fourth step, draw conclusions to be able to hone indicators of mathematical communication skills, namely expressing mathematical ideas through oral, written and visually describing them. So it can be concluded that RME can improve mathematical communication skills.Pendekatan pembelajaran Realistic Mathematics Education (RME) banyak digunakan untuk meningkatkan berbagai kemampuan dalam proses pembelajaran. Salah satunya adalah kemampuan komunikasi matematis. Tujuan penelitian ini adalah untuk mengetahui kontribusi pendekatan pembelajaran Realistic Mathematics Education (RME) dalam meningkatkan kemampuan komunikasi matematis. Jenis penelitian ini adalah penelitian kepustakaan (library study). Ada 32 sumber berupa buku, journal dan prosiding yang di editing, organizing dan penemuan hasil penelitian. Hasil yang diperoleh yaitu pada langkah pertama RME memahami masalah kontekstual mampu mengasah indikator kemampuan komunikasi matematis yaitu mengekspresikan ide-ide matematika melalui lisan, tulisan. Pada langkah kedua menyelesaikan masalah kontekstual mampu mengasah indikator kemampuan komunikasi yang kedua yaitu kemampuan memahami, menginterprestasikan, dan mengevaluasi ide-ide matematika. Pada langkah ketiga membandingkan dan mendiskusikan jawaban mampu mengasah indikator kemampuan komunikasi matematis ke tiga yaitu kemampuan menggunakan istilah, notasi matematika dan struktur-struktur untuk menyajikan ide, menggambarkan hubungan dan model situasi. Pada langkah keempat menarik kesimpulan mampu mengasah indikator kemampuan komunikais matematis satu yaitu yaitu mengekspresikan ide-ide matematika melalui lisan, tulisan serta menggambarkannya secara visual. Jadi dapat disimpulkan bahwa RME dapat meingkatkan kemampuan komunikasi matematis.